Fundamental Forces and Unified Field Theory - Tiwary, Dhananjay Kumar (Academic Voices: A Multidisciplinary Journal, 2011)
This paper deals with fundamental particles, their classifications on the basis of Bose – Einstein Statistics, Fermi- Dirac Statistics and Quark Theory along with four types of existing fundamental forces. This also reflects on unified field theory regarding unification of the fundamental forces. Keywords Bosons, fermions, quarks, Higgs’ particles, standard model DOI: http://dx.doi.org/10.3126/av.v1i0.5302 Academic Voices 2011; 1: 16-19